2014
DOI: 10.4236/jep.2014.514136
|View full text |Cite
|
Sign up to set email alerts
|

Distribution, Enrichment and Ecological Risk Assessment of Six Elements in Bed Sediments of a Tropical River, Chottanagpur Plateau: A Spatial and Temporal Appraisal

Abstract: Distribution and enrichment of six elements (iron, zinc, copper, lead, cadmium and manganese) in surface bed sediments, collected from seventeen selected locations during pre-monsoon and postmonsoon periods, of the tropical Chottanagpur plateau river Subarnarekha along with the ecological risks involved were investigated. Owing to the rich occurrence of mineral resources, the Subarnarekha river basin has a large scale presence of industrial and mining units especially in the Indian State of Jharkhand. An asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 32 publications
2
39
2
Order By: Relevance
“…In a recent study, the spatial and temporal investigation by Manoj and Padhy (2014) showed Cd as the contaminant of chief concern. Cd concentration was noted above its geochemical background value throughout the studied area in both study periods.…”
Section: Ecological Risk Assessmentmentioning
confidence: 99%
“…In a recent study, the spatial and temporal investigation by Manoj and Padhy (2014) showed Cd as the contaminant of chief concern. Cd concentration was noted above its geochemical background value throughout the studied area in both study periods.…”
Section: Ecological Risk Assessmentmentioning
confidence: 99%
“…Besides, physical land scope (gentle flat land), hydrological flow (gently river flows conditions) and clay dominated particles size might have facilitated the adsorption and deposition of suspended metals. Consequently, highest PLI value reflects that the quality of sediments at this sample site was highly deteriorated due to high anthropogenic metal inputs (Al Obaidy et al 2014;Likuku et al 2013;Manoj and Padhy, 2014;Sekbira et al 2010).…”
Section: Pollution Load Index (Pli)mentioning
confidence: 94%
“…Contamination factor is commonly used to demonstrate the level of contamination of sediment by particular toxic metal at a given sample site (Manoj and Padhy, 2014). It is defined as:…”
Section: Contamination Factor (Cf)mentioning
confidence: 99%
See 1 more Smart Citation
“…Some trace elements in Bacalar Lagoon sediments may reflect anthropogenic pollution. Here we used four indices following Manoj and Padhy (2014; see Table 3). We normalised concentrations to Al because it is a conservative lithogenic element and is resistant to chemical weathering; hence, it does not actively participate in the dominant geochemical cycles and does not have a significant anthropogenic source (Boës et al 2011;Dautović et al 2014).…”
Section: Sediment Pollutionmentioning
confidence: 99%